Metabolic Engineering of Yeast and Plants for the Production of the Biologically Active Hydroxystilbene, Resveratrol. (13th May 2012) - Jeandet, Philippe; Delaunois, Bertrand; Aziz, Aziz; Donnez, David; Vasserot, Yann; Cordelier, Sylvain; Courot, Eric
Abstract : Resveratrol, a stilbenic compound deriving from the phenyalanine/polymalonate route, being stilbene synthase the last and key enzyme of this pathway, recently has become the focus of a number of studies in medicine and plant physiology. Increased demand for this molecule for nutraceutical, cosmetic and possibly pharmaceutic uses, makes its production a necessity. In this context, the use of biotechnology through recombinant microorganisms and plants is particularly promising. Interesting results can indeed arise from the potential of genetically modified microorganisms as an alternative mechanism for producing resveratrol. Strategies used to tailoring yeast as they do not possess the genes that encode for the resveratrol pathway, will be described. On the other hand, most interest has centered in recent years, on STS gene transfer experiments from various origins to the genome of numerous plants. This work also presents a comprehensive review on plant molecular engineering with the STS gene, resulting in disease resistance against microorganisms and the enhancement of the antioxidant activities of several fruits in transgenic lines.